ADAPTASI MUSIMAN NELAYAN TRAMMEL NET DI PELABUHAN PERIKANAN SAMUDERA CILACAP - Agung Nugraha; Prihatin Ika Wahyuningrum; Domu Simbolon (Jurnal Teknologi Perikanan dan Kelautan, 2020)
Fishers, including trammel net fishers, have different respond due to seasonal changes. The research aims to calculate shrimp season index, to identify the impact of seasonal changes related to income of trammel net fishers, and to identify the adaptation pattern of trammel net fishers related to shrimp season changes. The data collected were trammel net fishing unit performance, trammel net fisherman adaptation methods, investment data, income, and fishermen's capital as well as trip data and trammel net shrimp production data for five years (2012-2016). Data analysis used fishing season index, fishing season impact related to income of fishers, and fishers adaptation to seasonal changes. The results showed that there are five months were identified as peak season of shrimp i.e. June, September, October, November, and December. Other results showed that seasonal changes have impacted to trammel net fishers income amounted Rp 6.185.800/vessel/trip. At the peak season fishing, fisher income were Rp 6.591.495/vssel/trip, however at the low season fishers income were Rp 405.695/vessel/trip. In addition there were five adaptation pattern related to seasonal changes of trammel net fishers which were 37% lending money and selling stuffs, 33% repairing fishing gear, 13% fishing gear diversification, 10% changing the fishing ground, and 7% income diversification. In conclution that fishers who choose adaptation pattern of fishing gear diversification have the highest income compared to fishers who choose other types of adaptation.